Kinship Terms in Surah An-Nisa A Semantic Study within the Framework of Semantic Component Theory (Al-Farooq Journal of Sciences, 2026)
This study examines kinship terms in Surat An-Nisā’ through a semantic analysis based on Componential Analysis Theory, which decomposes meaning into minimal distinctive features. The research aims to identify shared and contrastive semantic components among kinship terms and to reveal the semantic relations governing them within the Qur’anic context, such as contrast, proximity, inclusion, and polysemy. Adopting a descriptive-analytical approach, the study relies on componential tables as a methodological tool to ensure precision and consistency. The findings demonstrate that Surat An-Nisā’ presents a coherent semantic system of kinship terms, structured around features such as gender, lineage, degree, and relation by blood or fosterage, serving the legal and social objectives of the surah.